1996
DOI: 10.1016/0376-7388(96)00163-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion induced phase separation with crystallizable nylons. I. Mass transfer processes for nylon 4,6

Abstract: Mass transfer during membrane formation by means of phase inversion for a polymeric system with both a solid-liquid and a liquid-liquid equilibrium was studied on the basis of the theory developed by Reuvers and Smolders. During the first moments of immersion in the coagulation bath, the concentrations at the interface between bath and film are governed by the virtual liquid-liquid equilibrium. This equilibrium no longer exists at a larger time scale. The interfacial concentrations as a result of the local liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The propagation of the concentration profiles through the film is then hardly influenced by the already started phase separation. Since the composition path of the 20% solution [13] is already rather shallow it will become even more levelled out in time; the morphology of the final membrane can be thus expected to be quite homogeneous as indeed is observed, Two conditions can cause spherulites to stop growing. 1.…”
Section: Spherulitic Morphologymentioning
confidence: 80%
See 4 more Smart Citations
“…The propagation of the concentration profiles through the film is then hardly influenced by the already started phase separation. Since the composition path of the 20% solution [13] is already rather shallow it will become even more levelled out in time; the morphology of the final membrane can be thus expected to be quite homogeneous as indeed is observed, Two conditions can cause spherulites to stop growing. 1.…”
Section: Spherulitic Morphologymentioning
confidence: 80%
“…Almost immediately after immersion the growth of a layer consisting of crystalline units starts. In the concentration profiles [13] it can be observed that the interfacial polymer concentration is almost 50%. The concentrations at the growing crystal surface, as given by the crystallization line, gives an equilibrium concentration with a lower polymer content.…”
Section: Axialitic Morphologymentioning
confidence: 91%
See 3 more Smart Citations